Synthesis, biological activity of newly designed sulfonamide based indole derivative as anti-microbial agent - Khushbu Agrawal; Tarun Patel; Rajeshree Patel (Future Journal of Pharmaceutical Sciences, 2023)
Abstract Background In medicinal chemistry, indole and its derivative play an important role. Indole is gaining a lot of importance in medicinal chemistry due to its physiological activity which includes anticancer, antitubercular, antimicrobial, antiviral, antimalarial, anti-inflammatory activities, antileishmanial agents, anti-cholinesterase, and enzyme inhibitory. The spread of antimicrobial resistance becomes a threat to both humans and animals. Antimicrobial resistance has been declared in the top 10 global major health risks by WHO including reported data of 2020 of AMR with 3,106,002 confirmed infections in humans across 70 countries. Result In this present work some new sulfonamide-based indole derivatives were synthesized by using 1H-indole -2 carboxylic acid as a starting material. The structure of all synthesized sulfonamide-based indole derivatives was confirmed by 1H NMR and LCMS Spectroscopy. Conclusion All the synthesized compounds were screened for anti-microbial activity against Gram Positive Staphylococcus aureus, Bacillus megaterium, and Gram Negative Klebsiella pneumonia, Escherichia coli, Salmonellatyphiae , Shigella sp., Enterobacter aerogenes. Among gram-positive Staphylococcus aureus, and Bacillus megaterium. The compound shows activity against Staphylococcus aureus, and among all gram-negative bacteria against Klebsiella pneumonia shows good activity.